PROMATES Project: Training for primary school teachers - Suárez Valdés-Ayala, Zuleyka (2024)
This article reports the results of the experience developed during the year 2022 in the Promates project, which belongs to the School of Mathematics of the Costa Rica Institute of Technology (TEC) and aims to develop a training plan for primary school teachers at the national level, focused on strengthening their knowledge and skills in the use of software in the teaching and learning of mathematics, through active and meaningful learning that centers on teachers' experiences and their classroom practices, taking into account the pedagogical model of our institution. This is done with the objective of addressing the lack of specialized training in this discipline and the lack of specialized didactic resources in the technological area. Each semester, we worked with two groups of twelve teachers each for ten synchronous sessionsusing the Zoom platform. The use of applications such as GeoGebra, Scratch, Goconqr, Powtoon, Genially, among others, was taught. To carry out these trainings, students from the Teaching of Mathematics with Technological Environments (MATEC) program, from the School of Mathematics, played a fundamental role by participating in the trainings, explaining the functioning of the applications, or providing feedback to the teachers regarding certain tasks.At the end of the trainings, the teachers, through an anonymous evaluation, expressed their complete satisfaction with what they learned, as they were unaware that these applications could be adapted to the content taught in the I and II Cycles of general basic education, and that they were also free. These types of training sessions must continue to be carried out in order to train primary education teachers in the technological and mathematical field, so that they can present this subject in an engaging manner and thus help reduce the anxiety it generates, through the use of technological resources, educational games, and strategies that allow them to enhance learning.